Znaczenie ucieleśnione: Propozycje kręgu Lakoffa - Pawelec, Andrzej (Przestrzenie Teorii, 2007)
In this article I present the idea of "embodied meaning" as developed in the theory of conceptual metaphor by Lakoff and Johnson and in the theory of blending by Turner and Fauconnier. I argue that this approach - despite numerous disclaimers - is close to the generative program introduced by Chomsky, who distinguished the linguistic "surface structure" from the mental (and unconscious) "deep structure". I make the claim that this understanding of "embodied meaning" is less adequate than the hermeneutical interpretation of meaning as embodied in acts of interpretation.